MODEL SISTEM LOST AND FOUND PADA PENCARIAN BAGASI DI MASKAPAI PENERBANGAN - Hani Dewi Ariessanti; Muhamad Yusup2; Ifran Sanni (LPPM Unbaja, 2019)
Convenience in traveling through airlines that can carry passengers from one place to another quickly and safely and become the expectations of passengers. Therefore, the subject matter is a consideration including the security of luggage and this requires the ground handling company and various airlines to provide solutions to the increasing market demand for their needs using air transportation. Some of the problems that exist in the baggage tracer system are the role of the Lost and Found unit in the airline in handling passenger baggage irregularities and the steps taken by the Lost and Found unit to resolve cases of passenger baggage irregularities. the scope of the study is on baggage tracer systems on airlines. This study uses the software development method used is the SDLC method (System Development Life Cycle) focusing on modeling (analysis and design). The model described is the Lost and Found system of baggage searches on airlines that are expected to answer the problems that occur if there is loss of goods in the airplane baggage.